PENGUATAN KELEMBAGAAN PETANI PADI DALAM PENGAMBILAN KEPUTUSAN ADOPSI TEKNOLOGI IPB PRIMA - Khairunnisa Khairunnisa; Amiruddin Saleh; Oos M Anwas (Jurnal Penyuluhan, 2019)
Farmer institutional strengthening is an effort to improve farmers' adoption decisions on an innovation. Farmers who are members of farmer groups will find it easier to manage to know, want, and be able to implement innovation. This study aims to analyze the influence of farmer institutional strengthening on IPB Prima Technology adoption decisions by rice farmers. This study uses a quantitative and quantitative approach with survey methods and questionnaires as a data collection tool. Respondents in this study were all members of the farmer group who participated in IPB 3S variety rice cultivation activities, as many as 50 people. Data was collected in July 2018. Data were analyzed using Statistical Product and Service Solutions (SPSS) version 23 for descriptive statistics and inferential statistics. The results showed that farmers agreed that farmer institutions functioned as strengthening the institutional structure of farmers, increasing the capacity of members in the development of agribusiness and improving the institutional capacity of farmers in carrying out their functions. In the decision of farmers to adopt Prima IPB Technology, farmers have reused straw on agricultural land and have cultivated rice plants in accordance with IPB Best-Practice, but farmers have never decomposed straw using decomposers and are still rare in the application of agricultural mechanization. Improving the institutional capacity of farmers in carrying out their functions significantly influences the application of IPB Bio and the implementation of IPB Best-Practice. Furthermore, increasing the ability of members in the development of agribusiness, especially the efficiency of time, has a significant negative effect on reuse of straw, by burning straw on agricultural land.